1998
DOI: 10.1017/s0022112098001803
|View full text |Cite
|
Sign up to set email alerts
|

On phase kinks, negative frequencies, and other third-order peculiarities of modulated surface waves

Abstract: Numerous laboratory and field experiments on nonlinear surface wave trains propagating in deep water (Lake & Yuen 1978; Ramamonjiarisoa & Mollo-Christensen 1979; Mollo-Christensen & Ramamonjiarisoa 1982; Melville 1983) have showed a specific wave modulation that so far has not been explained by nonlinear theories. Typical effects were the so-called wave phase reversals, negative frequencies, and crest pairing, experimentally observed in some portions of the modulated wave train. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
1
8
0
Order By: Relevance
“…To satisfy the Laplace equation to second order, Yuen and Lake (1982), Voliak (1998), andHwung et al (2009) suggested an additional phase-shifted term with a linear and quadratic z correction in the representation of the potential function ϕ:…”
Section: Modulation Equations For One-dimensional Interactionmentioning
confidence: 99%
“…To satisfy the Laplace equation to second order, Yuen and Lake (1982), Voliak (1998), andHwung et al (2009) suggested an additional phase-shifted term with a linear and quadratic z correction in the representation of the potential function ϕ:…”
Section: Modulation Equations For One-dimensional Interactionmentioning
confidence: 99%
“…The solution to the problem, uniformly valid to O ( ɛ 3 ), is found by a two‐scale expansion with the differentiation: Substitution of the velocity potential in its linear form, ϕ = ϕ 0 e kz sin θ , satisfies the Laplace in the first order in ɛ due to and gives the following additional terms in the second order O ( ɛ 2 ): To satisfy the Laplace equation in the second order, Yuen and Lake [1982] and Shugan and Voliak [1998] suggested additional phase shifted term with a linear and quadratic z correction in the representation of the potential function ϕ : Exponential decaying of wave's amplitude with z is accompanied by the second order subsurface jet due to slow horizontal variations of the wave number and amplitude of the wave packet.…”
Section: Modulational Equations Of a One‐dimensional Interactionmentioning
confidence: 99%
“…yields the known wave action conservation law. Modulation – are closed by the equation of wave phase conservation that follows from as a compatibility condition [ Phillips , 1977]: The derived set of – in the absence of a current coincide with those of Shugan and Voliak [1998].…”
Section: Modulational Equations Of a One‐dimensional Interactionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a half a century a more efficient method of the investigation, namely, different-time scale method was developed [3,4]. Thereafter, investigations of nonlinear waves on the charged fluid surface directed to finding soliton solutions were also begun [5][6][7][8]. The effects of viscosity [9], electric charge [10] and its relaxation [11], surface active agent relaxation [12], fluid stratification [13], and tangential jump in the velocity field on the stratification boundary [14] on implementation of the nonlinear wave motion and location of internal nonlinear resonances were studied.…”
mentioning
confidence: 99%